A justiça na República de Platão - Silva, Rosemary Marinho da (2007)
The aim of this search is a concept of justice, and its arguments about cities and human soul, send from Plato in The Republic. The first aspect that it has been studied says that each person who does that it is according to the nature that belongs to and the function that it practice in the city, they are called fair person. This function is determinate by the virtue. One of them is the justice, virtue from virtues, linking functions and virtues in favor of common goodness. The second aspect determinates that functions and virtues find in soul as the same in the city. Therefore, the study about the presence of justice in the soul. The third aspect increases in the relation between function and virtue as in the city as in the soul, at the meaning of education, then if the reason controls the soul, the regent learns how to administrate the city into the contemplation of the idea about goodness, ordering the collectivity. The guardian, irascible part of the soul and auxiliary of the regent, through the courage, combat against any new that can prejudice the good development of the city. To the ordinary citizen, greed part of soul competes to accept such a order, which materializes in the work division. This concept, studied from three aspects. It is defined by the conflicts with other meanings of justice presents in Greece of IV age b.C. These conflicts are studied based on distinctions between Plato thoughts and sophistic teachings.